Dialogue In The Poetry Of Ibn Muqbil (A Reading Of The Aesthetics Of The Text)/ الحوار في شعر ابن مقبل (قراءة في جماليات النص) - Shakir, Marwah Ahmed (Ijaz Arabi Journal of Arabic Learning, 2024)
The dialogue represents an essential part of the aesthetics of the literary text, with the aesthetic interaction and multiplicity of voices within the text that it achieves. It helps to reveal the features of the creator's personality and its psychological tendencies. Through his conversation, the creator may look to show the characters who surrounded him, which may have affected his creative process. It psychologically impacted the creator and created an essential influence on the recipient. The method research is the theory of reading and reception and the mechanisms of the German theorist (Wolfgang Iser) in revealing the aesthetic effect of the creative artistic and poetic techniques that the text carries. The most important result of the research is that there is much dialogue in Ibn Muqbil's poetry, employing him to express psychological impulses such as grief, illness, and love toward the beloved woman or to complain about her. Dialogue contributed to the aesthetic of influence through artistic techniques that exposed creative poetics and the susceptibility of ancient texts to permanence, life, and harmony with theories of modernity (such as reading and receiving theory).